Viral Marketing Through social media and its Impact on Consumer Buying Behavior - Gatea, Qayssar Jabbar; Al-Rawi, Bushra Jameel (ALBAHITH ALALAMI, 2024)
Viral marketing relies on social relationships and creative messaging to establish a mutually beneficial relationship between organizations and their audiences, aiming to increase brand awareness at low costs and reach the largest number of customers. This research focuses on exploring the relationship between viral marketing for the brands "Apple and Samsung" through social media and consumer purchasing behavior. It examines the information sources that consumers rely on when researching product details before purchasing, the motivations that drive users to follow marketing posts on social media, and the viral marketing techniques and tactics that increase consumer loyalty to brands. The researcher employed a survey method using a questionnaire, selecting a "multi-stage random sample." The research sample size was 500 respondents from central Baghdad, on both sides of "Karkh and Rusafa," aged 18 and above, consisting of both men and women who are social media users. The findings revealed that a large percentage of the research sample shared posts, with "friends’ shares on their pages" being among the most attractive types of posts. This increases the sample’s familiarity with the brand, as respondents tend to share when they believe it benefits their friends. The majority of respondents also expressed increased trust when exposed to marketing messages from pages verified with a blue checkmark. Most agreed that the information provided by companies on their platforms is "sufficiently adequate," and their primary motivation for following such information was the inclusion of "offers and discounts," which was one of the key reasons driving them to make online purchases.